(untitled) (Journal of human and social sciences, 2022)
We live in what can rightly be called the age of science, where the adoption of the scientific method has sparked a rapid and continuous revolution through research activity. Since the seventeenth century, the scientific method has undergone significant development and wide dissemination, becoming by the twentieth century a defining feature of modern civilization. With the growing awareness of the role of science in improving human life, the prosperity of societies has increasingly depended on the application of scientific knowledge. However, despite the proliferation of universities and research centers, many developing countries remain behind, unlike advanced societies that have succeeded in establishing strong research foundations as the basis for their progress. This raises important questions about the real connection between science, education, and work, and how it can be harnessed to achieve genuine development in contemporary societies. The article seeks to clarify the dimensions of this relationship, especially in light of rising unemployment and growing criticism of educational systems. Drawing on existing scientific sources as well as the researcher’s own experience, the study emphasizes the need for a deeper understanding of how developed societies achieved progress and why many others still struggle.